Being open matters: the antecedents and consequences of cross-understanding in teams. Issue 1 (9th March 2015) - Meslec, Nicoleta; Graff, Daniel
Abstract : Purpose: – The aim of the current paper is to explore the role of cross-understanding as a mediator between openness to cognitive experience and reflective communication cognitions on the one hand and team performance on the other hand using the input-mediator-output-input (IMOI) model as a framework (Ilgen et al., 2005). Design/methodology/approach: – The sample consisted of 156 participants organized in 37 student teams. Two mediation models were estimated while using a nonparametric resampling procedure of bootstrapping developed by Hayes (2012). Findings: – Cross-understanding positively mediates the relation between openness to cognitive diversity and team performance and the relation between reflective communication cognition and team performance. Reflective communication cognition has a direct and negative relation to team performance. Additionally, the percentage of women within groups positively relates to group performance. Research limitations/implications: – Future research could explore the validity of this model in other organizational settings and while using different indicators for team performance. Practical implications: – Practitioners should encourage an open climate toward knowledge diversity and different perspectives within teams, as this might create the optimal conditions for cross-understanding to emerge. Team members should also be encouraged to learn not only about the knowledge of other team members but also about their beliefs, preferences and things they are sensitive to, as this awareness is beneficial for the overall team performance. Originality/value: – This paper contributes to the team cognition literature by bringing empirical support for a relatively less investigated concept: cross-understanding. The paper establishes its relation to team performance and two of its potential antecedents – openness to cognitive diversity and reflective communication cognition.